The ArcB kinase sensor participates in the phagocyte-mediated stress response in Salmonella Typhimurium - Pardo-Esté, Coral; Urbina, Francisca; Aviles, Nicolas; Pacheco, Nicolas; Briones, Alan; Cabezas, Carolina; Rojas, Vicente; Pavez, Valentina; Sulbaran-Bracho, Yoelvis; Hidalgo, Alejandro A.; Castro-Severyn, Juan; Saavedra, Claudia P. (Frontiers in Microbiology, 2025)
The ArcAB two-component system includes a histidine kinase sensor (ArcB) and a regulator (ArcA) that respond to changes in cell oxygen availability. The ArcA transcription factor activates genes related to metabolism, membrane permeability, and virulence, and its presence is required for pathogenicity in Salmonella Typhimurium, which can be phosphorylated independently of its cognate sensor, ArcB. In this study, we aimed to characterize the transcriptional response to hypochlorous acid (HOCl) mediated by the presence of the ArcB sensor. HOCl is a powerful microbicide widely used for sanitization in industrial settings. We used wild-type S. Typhimurium and the mutant lacking the arcB gene exposed to NaOCl to describe the global transcriptional response. We also infected murine neutrophils to evaluate the expression levels of relevant genes related to the resistance and infection process while facing ROS-related stress. Our results indicate that the absence of the arcB gene significantly affects the ability of S. Typhimurium to grow under HOCl stress. Overall, 6.6% of Salmonella genes varied their expression in the mutant strains, while 8.6% changed in response to NaOCl. The transcriptional response associated with the presence of ArcB is associated with metabolism and virulence, suggesting a critical role in pathogenicity and fitness, especially under ROS-related stress. Our results show that ArcB influences the expression of genes associated with fatty acid degradation, protein secretion, cysteine and H2S biosynthesis, and translation, both in vitro and under conditions found within neutrophils. We found that protein carbonylation is significantly higher in the mutant strain than in the wild type, suggesting a critical function for ArcB in the response and repair processes. This study contributes to the understanding of the pathogenicity and adaptation mechanisms that Salmonella employs to establish a successful infection in its host.